"Toxic pleasures": A study of eating out behavior in Arab female university students and its associations with psychological distress and disordered eating. (December 2018) - Al-Thani, Maryam A.; Khaled, Salma M.
Abstract: University years are a critical period in which young people establish independence and adopt lasting health behaviors. The aim of this study was to estimate the associations between eating out, psychological distress, and disordered eating behaviors among young Arab females in Qatar a rapidly developing small nation. A cross-sectional probability-based survey of 1615 Qatar University's female students assessed the frequency of eating out (main independent variable) and other eating behaviors in relation to two main dependent variables, disordered eating and psychological distress, which were measured using the Eating Attitudes Test and the Kessler Psychological Distress Scale, respectively. Multivariable logistic-regression analyses were used to estimate these two main associations with and without adjustment for other potential confounding variables, including the main effects of psychological distress and disordered eating on each other. Of the students, 45% reported eating out 3 times or more a week. Furthermore, approximately 18% screened positive for disordered eating and 33% reported high levels of psychological distress in the past 30 days. After adjustment for other variables, eating out 5 times or more a week was not significantly associated with the odds of disordered eating (OR 1.21, p = 0.32). However, eating out 5 times or more per week was significantly associated with odds of having psychological distress (OR 1.46, p = 0.03). Both psychological distress and disordered eating were strongly associated with each other (OR 2.58, p < 0.001). Highlights: We explored the association between frequency of eating out, disorderedeating, and psychological distress Higher frequency of eating out was strongly associated with psychologicaldistress, but not disordered eating in this traditional setting Psychological distress and disordered eating were strongly associated witheach other Higher BMI was associated with disordered eating and psychologicaldistress, but not with frequent eating out behavior These associations may be part of early changes that predispose youngfemale adults to obesity and eating disorders